Improved Solubility and Dissolution Rate of Ketoprofen by the Formation of Multicomponent Crystals with Tromethamine - Lili Fitriani; Wahyu Alfath Firdaus; Wahyu Sidadang; Henni Rosaini; Okky Dwichandra Putra; Hironaga Oyama; Hidehiro Uekusa; Erizal Zaini (Crystals, 2022)
This study aims to improve the dissolution rate of ketoprofen by preparing multicomponent crystals with tromethamine. The multicomponent crystals (equimolar ratio) of ketoprofen and tromethamine were prepared by the solvent co-evaporation method. The solid-state properties of the resulting powder were characterized by powder X-ray diffraction, DSC thermal analysis, FT–IR spectroscopy, solubility, and in vitro dissolution rate. The crystal structure of the multicomponent crystal was determined by single-crystal X-ray diffraction analysis. The results showed that the powder X-ray diffraction pattern of the ketoprofen–tromethamine binary system was different from that of the starting materials. This difference indicates the formation of a new crystalline phase between ketoprofen and tromethamine (equimolar ratio). The DSC thermogram of the ketoprofen–tromethamine binary system exhibited a single and sharp endothermic peak at 128.67 °C, attributed to the melting point of a multicomponent crystal of ketoprofen–tromethamine. A single-crystal X-ray analysis revealed that ketoprofen–tromethamine formed a layered structure, salt-type multicomponent crystal. The solubility and dissolution rate of the multicomponent crystal were notably enhanced compared to the intact ketoprofen. The ketoprofen–tromethamine binary system forms salt-type multicomponent crystals, which can significantly increase the solubility and dissolution rate.